2013
DOI: 10.3989/revmetalm.1226
|View full text |Cite
|
Sign up to set email alerts
|

Estudio del rendimiento del torneado de alta velocidad utilizando el coeficiente de dimensión volumétrica de la fuerza de corte resultante

Abstract: This work deals with the experimental study of the resultant cutting force evolution of two coating carbide and a cermet inserts, during the dry turning of AISI 1045 steel with 400, 500 and 600 m/min cutting speeds. A new criterion for machinability study, the coefficient of volumetric dimension of cutting force, it is introduced. The investigation showed a better performance of cermet for moderate and intermediate cutting speeds, while at high cutting speed and final machining time, the three layers coated ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The depth of cut (a = 0.5 mm) and feed rate (f = 0.1 mm/r) were kept constant. The cutting conditions used in the experiments were selected according to the review of the scientific literature [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. These are described in Table 3.…”
Section: Experimental Setup and Factorial Design Of The Investigationmentioning
confidence: 99%
See 1 more Smart Citation
“…The depth of cut (a = 0.5 mm) and feed rate (f = 0.1 mm/r) were kept constant. The cutting conditions used in the experiments were selected according to the review of the scientific literature [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. These are described in Table 3.…”
Section: Experimental Setup and Factorial Design Of The Investigationmentioning
confidence: 99%
“…Stachurski et al [22] reported an assessment of the effect of selected conditions on the value of the cutting force during turning of AISI 1045 steel with and without cutting fluid. Hernández et al [23] analyzed the resultant cutting force evolution in high speed turning of AISI 1045 steel with two coated carbide and a cermet inserts, but the authors did not include the tool flank wear. Qasim et al [24] presented an optimization of process parameters for high-speed machining of AISI 1045 steel, using several cutting tools, with the objective of reducing cutting forces and temperature.…”
Section: Introductionmentioning
confidence: 99%